2023
DOI: 10.3332/ecancer.2023.1535
|View full text |Cite
|
Sign up to set email alerts
|

Durable effect of imatinib and metronomic chemotherapy with capecitabine in pancreatic carcinoma

Abstract: Background: Pancreatic ductal carcinoma (PDC) is a challenging diagnosis with a particularly poor prognosis, even after curative surgery (median survival: <30 months). The prognosis of borderline resectable pancreatic cancer (BR-PDC) is even worse. We describe a patient with BR-PDC who achieved stable disease with metronomic chemotherapy after refusing surgery.Case presentation: A 75-year-old woman was presented with jaundice and epigastric pain. Imaging confirmed a mass in the pancreatic head encasing the sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
0
0
Order By: Relevance
“…Quality evaluation was performed in our meta-analysis using the Cochran's risk of bias assessment and it was found that the evaluation of scores in RCT showed a good value but, some unclear risk of selection bias was found in one of the studies 18 . All the single-arm studies showed scored good scores (between [11][12][13][14][15][16][17][18][19].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Quality evaluation was performed in our meta-analysis using the Cochran's risk of bias assessment and it was found that the evaluation of scores in RCT showed a good value but, some unclear risk of selection bias was found in one of the studies 18 . All the single-arm studies showed scored good scores (between [11][12][13][14][15][16][17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…The evaluation of scores in RCT showed a good value in Cochran's risk of bias assessment, but, some unclear risk of selection bias was found in the study done by Zeng et al 18 . Figure 2 All the single-arm studies scored good scores (between [11][12][13][14][15][16][17][18][19] which suggests good quality studies (Table 1). The mean age of the patients was reported in two studies and they were found to be 66.7 ± 10.0 in the study done by Filippo et.…”
Section: Quality Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation